Sustainable business model innovation and perspective of using microalgae to produce biofuel : a systematic literature review - Moshood, Taofeeq Durojaye; Nawanir, Gusman; Mohd Hanafiah, Ahmad; Lee, Khai Loon; Suhaidah, Hussain (Universiti Malaysia Terengganu, 2022)
The dependence on fossil oil has led to the search for alternative renewable energy resources, such as biomass, which has climbed to the top of the list of renewable energy solutions. It is not possible to separate these energy issues from environmental and sustainability concerns. Developing sustainable practices is essential for the continued expansion of countries’ and the world’s energy resources. The capacity to transition into new market models rapidly and efficiently is a critical source of sustained competitive advantage and leverage for increasing biofuel microalgae production sustainability. Given the issue’s importance, the causes of failure are mostly unknown, and there is only a limited thorough description of the sustainable business model innovation process in the literature. This study conducts a comprehensive review of the literature on the idea and technique of sustainable innovation in the microalgae business model. Multiple process phases of sustainable business model creation are described with a thorough list of major difficulties and obstacles connected with each step of the process. This study also looks into how management tools may be transformed into a process system and some insights into the process’s operational setup and performance variables.